2019
DOI: 10.1055/a-0958-2148
|View full text |Cite
|
Sign up to set email alerts
|

EUS-guided fiducial marker placement for radiotherapy in rectal cancer: feasibility of two placement strategies and four fiducial types

Abstract: Background and study aims  To facilitate image guidance during radiotherapy of rectal cancer, we investigated the feasibility of fiducial marker placement. This study aimed to evaluate technical success rate and safety of two endoscopic ultrasound (EUS)-guided placement strategies and four fiducial types for rectal cancer patients. Patients and methods  This prospective multicenter study included 20 participants who were scheduled to undergo rectal cancer treatment with neoadjuvant short-course radiotherapy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Previous studies on fiducial insertion in the rectum report no serious adverse events. 22,24,25 In one study, a small amount of bleeding that resolved spontaneously was reported in 1 out of 54 patients. 23 A limitation of this study is the small number of patients.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Previous studies on fiducial insertion in the rectum report no serious adverse events. 22,24,25 In one study, a small amount of bleeding that resolved spontaneously was reported in 1 out of 54 patients. 23 A limitation of this study is the small number of patients.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, a total of 64 fiducials were inserted, of which 35 fiducials were still in situ at the end of radiation therapy. 24 Furthermore, the insertion of fiducials is an invasive procedure. Previous studies on fiducial insertion in the rectum report no serious adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations